(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study uses a qualitative approach with descriptive methods. Data was obtained through in-depth interviews with three main sources, namely the club owner, coach, and athletes. Data analysis was carried out through a process of reduction, data presentation, and conclusion drawing, which was then visualized in the form of a Word Tree, Word Cloud, Bar Chart, and Project Map to strengthen the interpretation of the research results. The results of the study show that athlete training at the Merangin Swimming Club not only focuses on improving technical aspects but also involves social support, motivation, and character building. The coach acts as a role model who provides technical and moral guidance, while the family is a source of emotional and financial support for the athletes. The main obstacles faced by the club include limited funds, uneven parental participation, and limited facilities. The results of this study show that the Merangin Swimming Club has succeeded in creating a collaborative and sustainable training system, which not only produces accomplished athletes but also shapes a healthy, disciplined, and characterful younger generation.